Efeito da interação de Trissolcus basalis e Telenomus podisi (Hymenoptera: Scelionidae) na efetividade do controle biológico de Euschistus heros (Hemiptera: Pentatomidae) - Bon, Victor José (2021)
Telenomus podisi and Trissolcus basalis are two important parasitoids used as biological control agents for the brown soybug, Euschistus heros. The interaction between these parasitoid species at the field, however, can result in different effectiveness of pest control, depending on the density of the species present and the conditions in which the species find their hosts at the field. This study aimed to analyze the effects of the complexity of interactions that can arise when two parasitoid species interact directly or indirectly during the foraging by E. heros eggs. Through experimental scenarios, the effects of intra and interspecific competition were evaluated in two moments: (i) during simultaneous exploration of parasitoids, that is, when female parasitoids compete directly for non-parasitized eggs and (ii) during sequential exploration of parasitoids, when femeles have found some already parasitized eggs among the available host´s eggs, resulting in offspring competition inside of host egg. In this scenario, female´s behavior was observed for 35minutes, allowing to evaluate the frequency of ovipositions in parasitized eggs. The effects of different type and time of competition interactions between parasitoides on the parasitism rates, viability and emergence patterns of the offspring were evaluated. For simultaneous exploration of parasitoids, the best scenario for control with high rates of emergence rates occurred when T. podisi was the only parasitoid species present in the system. In the presence of T. basalis, the rates of parasitism remained high only when T. podisi was also present, although the emergence rates has been considerably reduced due to multiparasitism. In sequential exploration of parasitoids, T. podisi showed higher rates of parasitism and emergence of offspring due to the greater ability to discriminate eggs previously parasitized by conspecifics. In this scenario, the offspring of the previous parasitism were more successful, however, the competitive interactions inside of eggs led to changes in the patterns of the emergence of the species, as well as the high mortality of the offspring. The type of competition present in parasitoid populations and the time in which it occurs (simultaneous or sequentially) can have direct impact on the effectiveness of short and long-term pest control.